Magnetic, Dielectric And Microstructural Properties Of Nickel−Zinc Ferrite Ni0.8zn0.2fe2o4 Prepared Via Conventional And Co-Precipitation Techniques - Jahanbin, Tania (2009)

(untitled)
Nickel-zinc ferrite is a soft magnetic material having low magnetic coercivity and high resistivity values. The high electrical resistivity and excellent magnetic properties make this ferrite an automatic choice as a core material for power transformers in electronic and telecommunication applications in megahertz frequency regions .The properties of the Ni–Zn ferrite are very sensitive to the method of preparation, sintering temperature, sintering time and chemical composition . Most ferrites prepared via the conventional ceramic processing method have some drawbacks. Wet chemical methods are being pursued to overcome these drawbacks and to produce ultra-fine, homogeneous and reproducible ferrite powders using aqueous solutions of salts of constituent ions. In this study, Ni0.8Zn0.2 Fe2O4 was prepared via both conventional ceramic and the co-precipitation methods. The microstructure, magnetic and dielectric properties The permittivity in both the co-precipitation synthesis and the conventional synthesis increases with increasing sintering temperature. The dielectric constant and loss tangent of sample prepared via co- precipitation is much lower than the conventional due to the smaller grain size and higher porosity. The resistivities of samples prepared via co-precipittion were from 7.2x108 to 3.7x108 (Ωcm) and 4.3x106 to 8.2x105 (Ωcm) for samples prepared via conventional synthesis. In small grain microstructure the grain boundaries are more thus increase the resistivity. This resulted higher resistivity in co-precipitation than conventional methods. The highest saturation magnetisation, Ms, values in samples synthesized by co- precipitation was 63 Ms(Am2kg-1) and 60 Ms(Am2kg-1) for the conventional counterpart which were sintered at 1300°C. The higher Ms in co-precipitation is probably due to better crystalline structure. The coercivity and remanence of samples prepared via co-precipitation are lower than those of the conventionally synthesized samples. The initial permeability value lies between 4 and 17 for the co-precipitation and 14 to 24 for conventional synthesis. The widest frequency range is obtained at 700°C in co-precipitation method due to the small grin size. The relative loss factor (RLF) also studied and it was revealed that the RLF increased with sintering temperature. But It is thus concluded that it is the better of the two methods of preparation employed in this work for Nickel-Zinc Ferrite, Ni0.8 Zn0.2 Fe2 O4.